Courses
Courses for Kids
Free study material
Offline Centres
More
Store

# If ${a_n} = 3 - 4n,$then show that ${a_1},{a_2},{a_3}.......$ form an A.P. Also find ${S_{20}}$.

Last updated date: 22nd Jun 2024
Total views: 414.6k
Views today: 4.14k
Answer
Verified
414.6k+ views
Hint: We will find the common difference of the series by taking any two consecutive terms let us say ${{\text{r}}^{{\text{th}}}}$ and ${(r - 1)^{th}}$ terms i.e., we’ll find the value of ${a_r} - {a_{r - 1}}$, if it comes out to be constant the given series will form an A.P. as an A.P. have a constant common difference throughout the series.
To find the sum of the first 20 terms of the series we’ll use the formula of the sum of first n terms of an A.P.

Complete step by step solution:
Given data: ${a_n} = 3 - 4n,$
Let a random term and its preceding term to find the common difference of the series
Let's take ${{\text{r}}^{{\text{th}}}}$ and ${(r - 1)^{th}}$ terms
${{\text{a}}_{\text{r}}}{\text{ = 3 - 4r}} \\ \Rightarrow {{\text{a}}_{{\text{r - 1}}}}{\text{ = 3 - 4(r - 1)}} \\ \Rightarrow {{\text{a}}_{{\text{r - 1}}}}{\text{ = 3 - 4r + 4}} \\ \Rightarrow {{\text{a}}_{{\text{r - 1}}}}{\text{ = 7 - 4r}} \\$
Now common difference say d,
${\text{d = }}{{\text{a}}_{\text{r}}}{\text{ - }}{{\text{a}}_{{\text{r - 1}}}} \\ \Rightarrow {\text{d = 3 - 4r - (7 - 4r)}} \\ \Rightarrow {\text{d = 3 - 4r - 7 + 4r}} \\ \Rightarrow {\text{d = - 4}} \\$
Putting the values of ${a_r}$ and ${a_{r - 1}}$
Since the common difference(d) is constant, it can be said that ${a_1},{a_2},{a_3}.......$ will form an A.P.
Using ${a_n} = 3 - 4n,$
Putting $n = 1$,
${{\text{a}}_{\text{1}}}{\text{ = 3 - 4(1)}} \\ \therefore {{\text{a}}_{\text{1}}}{\text{ = - 1}} \\$
Putting $n = 2$,
${{\text{a}}_{\text{2}}}{\text{ = 3 - 4(2)}} \\ \therefore {{\text{a}}_{\text{2}}}{\text{ = - 5}} \\$
Putting $n = 3$,
${a_3} = 3 - 4(3) \\ \therefore {a_3} = - 9 \\$
Therefore, the A.P. will be -1,-5,-9……….
Now, Sum of first n terms of an A.P. i.e. ${S_n}$is given by,
${S_n} = \dfrac{n}{2}\left[ {2a + \left( {n - 1} \right)d} \right]$
Using this formula, we get,
${S_{20}} = \dfrac{{20}}{2}\left[ {2{a_1} + \left( {20 - 1} \right)( - 4)} \right]$
Using ${a_n} = 3 - 4n,$we get,
$= 10\left[ {2(3 - 4(1)) + 19( - 4)} \right] \\ = 10\left[ {2(3 - 4) - 76} \right] \\ = 10\left[ {2( - 1) - 76} \right] \\ = 10\left[ { - 2 - 76} \right] \\ = 10\left[ { - 78} \right] \\ = - 780 \\$
Therefore,
${S_{20}} = - 780$

Hence, the AP is -1,-5,-9,…….. and ${S_{20}} = - 780$

Note: We can also find the value of ${S_{20}}$ using the alternative formula for the sum of first n terms of an A.P. can also be written as
${S_n} = \dfrac{n}{2}\left[ {a + {a_n}} \right]$
Using ${a_n} = 3 - 4n,$we get
${S_{20}} = \dfrac{{20}}{2}\left[ {{a_1} + {a_{20}}} \right] \\ = \dfrac{{20}}{2}\left[ {3 - 4(1) + 3 - 4(20)} \right] \\ = 10\left[ {3 - 4 + 3 - 80} \right] \\ = 10\left[ {6 - 84} \right] \\ = 10\left[ { - 78} \right] \\ = - 780 \\$